THE ECONOMIC ROLE OF COMMUNITY WITH MEDIUM SMALL MICRO BUSINESSES IN INCREASING PEOPLE'S WELFARE - Rochmatillah, Rochmatillah (Elastisitas : Jurnal Ekonomi Pembangunan, 2019)
Prosperous and prosperous people in a country can be seen from how the function of the country is, because creating prosperity and prosperity for the people is a function and purpose of the establishment of a country. We already know that in Indonesia there are still many gaps between "Rich" and "Poor" which shows that our country must work harder and even be smarter in order to improve the welfare and prosperity of its people. Likewise with the people's welfare, it is undeniable that the country's economy is one of the determinants of the welfare of its people. In this article, we will discuss the linkages between popular economy, micro, small and medium enterprises, and improving people's welfare.In this article, we will discuss the linkages between popular economy